Pengaruh Penggunaan Aplikasi Belajar Terhadap Kemampuan Literasi Awal Anak Usia 5-6 Tahun - Dwi Jihan Kiliu; Sri Wahyuningsi Laiya; Icam Sutisna (Jurnal Pendidikan dan Sastra Inggris, 2025)
Early literacy skills in reading are an important foundation for early childhood development. Observations at Palam State Kindergarten showed that out of 23 children, 15 still had difficulty recognizing letters and reading simple syllables. This study investigates how learning apps influence the early literacy development of 5-6-year-old children at Palam State Kindergarten, North Tinangkung District, Banggai Islands Regency. The method used in this study is a quantitative experiment with a one-group pretest-posttest design on 23 children in group B. The results showed a significant increase, where the average pretest score of 20.91 (category "starting to develop") increased to 32.73 in the posttest (category "developing as expected"). The t-test showed a calculated t value of 36.42 > t table 1.717 (α = 0.05), so Ho was rejected and Ha was accepted. Thus, it can be concluded that the use of learning applications significantly influences the early literacy skills of children aged 5-6 years at Palam State Kindergarten, North Tinangkung District, Banggai Islands Regency.